Weed effects on the establishment and nutritive value of pastures with different annual/perennial ratio - Lavarello Herbin, Agustina (2020)
Livestock intensification is increasing weed invasion in pastures. We performed an experiment near Buenos Aires, Argentina, to evaluate the impact of weeds on temperate cultivated pastures. We sowed 1,700 viable seeds m–2 in 24, 1.5‐m2 plots. Each plot had seven sowed lines, three of legumes (red clover, Trifolium pratense L.; 50% of seeds) alternating with four of grasses arranged in two sowing designs differing in the annual/perennial ratio: 70% prairie grass (Bromus willdenowii Kunth, Bw, annual species) + 30% of orchardgrass (Dactylis glomerata L., Dg, perennial species) (>Bw), or 30% of Bw + 70% of Dg (>Dg). In the inter‐lines of each plot, we sowed the weed brown mustard (Brassica juncea L.) at four growing densities. At 123 d after sowing, we harvested aerial biomass of weeds and forage species (legume biomass was almost negligible at this date). We quantified aboveground net primary production (ANPP) of weeds and grasses (separated into blades, sheaths, and blades + sheaths), tiller density (indicating potential persistence), blade crude protein (CP), and neutral detergent fiber (NDF) concentrations of grasses.We made regressions to analyze the direct effect of weed biomass on each grass species, their indirect effects on the proportion of each species in the pasture, and their net effects on both species taken together. Weeds had negative direct and net effects. However, they did not have any indirect effect on species proportion. Pastures with lower annual/perennial ratio were more productive and potentially more persistent. Weeds also directly increased blade CP of the annual species.